Rancang Bangun Aplikasi Sistem Pemesanan Konsumen Pizza Hut Delivery Tulungagung Berbasis Website dengan Teknologi Quick Response Code (QR) - Safikri, Daffy; Faizah, NM; Karo-Karo, Panser (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2024)
Pizza Hut Delivery is a retail company operating in the fast-food sector. In the manual ordering system, customers must either visit the outlet for take-away or call the call center for home delivery. This study aims to provide a solution for the Pizza Hut Delivery outlet in Tulungagung, allowing customers to place orders online. Through this system, customers can order directly via their gadgets or smartphones for both take-away and delivery services. The research utilizes the waterfall model with PHP as the programming language and MySQL as the database server for data storage. The system is also equipped with Quick Response (QR) Code technology, enabling easy access to the Pizza Hut Delivery Tulungagung ordering website.